2007
DOI: 10.1172/jci32032
|View full text |Cite
|
Sign up to set email alerts
|

Gas1 is a modifier for holoprosencephaly and genetically interacts with sonic hedgehog

Abstract: Holoprosencephaly (HPE) is a clinically heterogeneous developmental anomaly affecting the CNS and face, in which the embryonic forebrain fails to divide into distinct halves. Numerous genetic loci and environmental factors are implicated in HPE, but mutation in the sonic hedgehog (Shh) gene is an established cause in both humans and mice. As growth arrest-specific 1 (Gas1) encodes a membrane glycoprotein previously identified as a Shh antagonist in the somite, we analyzed the craniofacial phenotype of mice har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 60 publications
9
138
0
Order By: Relevance
“…Hhinteracting protein (HIP) can compete with PTC in Hh binding to inhibit Hh signaling (Chuang and McMahon, 1999). Additional molecules, Ihog (or its vertebrate homologs CDO and BOC), GAS1 and Glypican-3, are also able to bind Hh (Okada et al, 2006;Tenzen et al, 2006;Yao et al, 2006;Zhang et al, 2006;Allen et al, 2007;Martinelli and Fan, 2007;Seppala et al, 2007;Capurro et al, 2008) although the Hh-Ihog binding mode is very different from Shh-CDO interaction (McLellan et al, 2008). It is still not entirely clear how binding of Hh proteins results in the pathway activation.…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…Hhinteracting protein (HIP) can compete with PTC in Hh binding to inhibit Hh signaling (Chuang and McMahon, 1999). Additional molecules, Ihog (or its vertebrate homologs CDO and BOC), GAS1 and Glypican-3, are also able to bind Hh (Okada et al, 2006;Tenzen et al, 2006;Yao et al, 2006;Zhang et al, 2006;Allen et al, 2007;Martinelli and Fan, 2007;Seppala et al, 2007;Capurro et al, 2008) although the Hh-Ihog binding mode is very different from Shh-CDO interaction (McLellan et al, 2008). It is still not entirely clear how binding of Hh proteins results in the pathway activation.…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…To address this issue, compound mutants between Gas1 and Shh were generated to test for a potential genetic interaction, and we discovered that Gas1 is a bona fide genetic modifier of Shh in the multiple developmental systems examined, including the craniofacial structure, heart, spinal cord, somite and limb. 30,33 Using a battery of cell type-specific molecular markers as readouts for HH signaling in these compound mutants, 30,31 it was found that from the genotypes of Gas1 -/-, Gas1 -/-;Shh +/-, Shh -/-, to Gas1 -/-;Shh -/-, there is a progressive reduction in HH signaling (relative to wild type and Gas1 +/-;Shh +/-controls). These data indicate that, contrary to the original expectations, Gas1 acts positively rather than negatively in HH signaling.…”
Section: Discovery Of a Gas1 Ligandmentioning
confidence: 99%
“…52 Gas1 or Cdo single mutant mice have microform holoprocencephaly, a phenotype that is further exacerbated in the Shh +/-background. 30,31,33,[40][41][42] Are Gas1 and Cdo modifier loci that contribute to the large spectrum of holoprosencephaly in humans? Conversely, increased SHH signaling, either by reducing PTC1 activity or increasing SHH, SMO, or GLI activities, leads to several types of tumors such as basal cell carcinoma, medullablastoma and prostate cancer.…”
Section: Human Diseasementioning
confidence: 99%
“…mice die immediately after birth. [89][90][91] The K.O. mice develop several defects including decreased cell proliferation in cerebellum, morphological alterations in the gastrointestinal tract and microform holoprosencephaly associated with multiple craniofacial defects.…”
Section: Gas1 Protein Structure and Expressionmentioning
confidence: 99%
“…mice develop several defects including decreased cell proliferation in cerebellum, morphological alterations in the gastrointestinal tract and microform holoprosencephaly associated with multiple craniofacial defects. [72,[89][90][91][92][93] The defects in Gas1-/-mice, are associated with the loss of the signaling induced by Sonic hedgehog (Shh). Interestingly, some patients with holoproscencephaly present mutations in the Gas1 gene with or without additional mutations on the Shh gene.…”
Section: Gas1 Protein Structure and Expressionmentioning
confidence: 99%